Vascular malformations in the maxillofacial region - M. Jafari (Tehran University of Medical Sciences, 1994)
Congenital vascular lesions occur most often in children. Parents of these children take them to maxillofacial surgeons directly or during the treatment of other complications such as infection or jaw bone disorders. Various terms now used are unable to describe the pathogenesis and mechanism of the effect of vascular lesions on growth and development of facial bone.  Term of hemangioma is used in almost all cases of congenital and acquired vascular lesions, while fibrosis or shrinkage occurs in some of these lesions over the time. There is also some confusion in describing the vascular lesions which primarily affected bones and soft tissue vascular malformations associated with changes in hard tissues.